Akumulasi Logam Berat pada Sedimen Matriks di Perairan Pekalongan - Arviani, Ilma Azizah; Sarasati, Wulandari; Hafidzah, Maudia Tri; Mulyono, Ridho Adi; Fasiroh, Alzarotun (MAIYAH, 2024)
Pekalongan waters have various problems, both from natural disasters, there is tidal floods and problems caused by anthropogenic activities, due to the large number of textile industries that dominate that dominate in this area, as a source of batik waste, even though in batik coloring several dyes are obtained of chemicals containing heavy metals are used. Batik waste contains metals such as Chromium (Cr), Cuprum (Cu), Manganese (Mn) and many other heavy metals on a small scale. Heavy metals can be buried in sediments and even take a long time to decompose. Therefore, further research is needed regarding the content of heavy metals in Pekalongan Waters so that the public can find out the effect of these heavy metals. The sampling method used was purposive random sampling, namely by selecting the points that were used as representatives of the research location. Assessment of heavy metals in sediments is carried out by comparing values ​​with quality standards and several analytical methods, there are Contamination Factor (CF), Enrichment factor (EF), Geo-Accumulation Index (I-geo), Potential Ecological Risk Index (PERI). The results of the study showed that Pekalongan waters at the research location were categorized as unpolluted to moderately polluted based on the content of heavy metals Cr and Cu. Based on the Mn content, these waters were polluted at almost all stations, on the contrary based on the Pb content this area was not polluted at all stations. Based on calculated the CF value of Pekalongan waters have a low to moderate contamination category, as well as from the EF value there is a low enrichment level, and if seen from the I-geo value are not polluted and from the PERI value the lavel of contaminatin risk is still low.